Feelings, Stress, and Adaptation Strategies of Nurses against COVID-19 in Guayaquil - Franco Coffré, Joicy Anabel; Leví Aguirre, Patricia de los Ángeles (Investigación y Educación en Enfermería, 2020)
Objective. To explore the feelings, stress factors, and adaptation strategies of nurses during the COVID-19 pandemic in Guayaquil, Ecuador. Methods. A cross-sectional, descriptive quantitative study, conducted through the application of a 52-item questionnaire with four sections (feelings, perceived stress, stress-reducing factors, and adaptation strategies). The study population was 227 nursing professionals from “Hospital General del Guasmo Sur” of the Ministry of Public Health, who worked during the peak of the pandemic from March to May 2020. The sample comprised 155 nurses who voluntarily accepted to participate. The study received 127 complete questionnaires for analysis. Results. The data showed the priority of humanist feelings and professional duty for these nurses, mostly young (59% under 35 years of age and with the professional exercise of three and fewer years), against the fear of contagion and the stress of strenuous work. They also revealed the great importance for them of the institutional support, recognition to the staff, and strict organization of safe care, like strategies for coping with this difficult experience. Conclusion. The COVID-19 pandemic represented for nurses from Guayaquil a great professional and emotional challenge. Health services and society could consider these findings to avoid burning out nurses and their professional desertion.